7-y-y=(-1)

Simple and best practice solution for 7-y-y=(-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-y-y=(-1) equation:


Simplifying
7 + -1y + -1y = (-1)

Combine like terms: -1y + -1y = -2y
7 + -2y = (-1)
7 + -2y = -1

Solving
7 + -2y = -1

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + -2y = -1 + -7

Combine like terms: 7 + -7 = 0
0 + -2y = -1 + -7
-2y = -1 + -7

Combine like terms: -1 + -7 = -8
-2y = -8

Divide each side by '-2'.
y = 4

Simplifying
y = 4

See similar equations:

| x(x+6)-40=0 | | 10x-6+18x-6(2x-4)=2 | | 2(x-3)=5(x-6) | | 4x-23=27 | | 2(2x+1)-3x=-6 | | 1.6/0.9=z/7.9 | | 6-5(2x+1)=11 | | 10x^2-390=0 | | 10x^2-139x-390=0 | | 5-(2x+3)=-25 | | 3x-7=9x+4 | | (2+7i)(8+i)= | | 10/6=30/t | | ln(x)-5=7.2 | | 30/x=6/7 | | 4x+(2x)-(2x)=72 | | y=2x^2+16x+38 | | 12+x=-6(7x-2) | | 16/20=72/x | | (3+8i)(7+i)= | | 10y^2+26y+12=0 | | (-4+5i)-(-7+5i)= | | (-2+6i)-(-7+6i)= | | x=300+50x | | 2y-35=5(y-4) | | (9+3i)+(8-2i)= | | 45w+126=9 | | c=300+50x | | 9(y-1)=-7y+7 | | y*0.17+(1-y)*0.7=0.15 | | 126w-45=9 | | 3u-15=5(u-7) |

Equations solver categories